2018
DOI: 10.1021/acs.est.7b05518
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Tracking of Highly Toxic Intermediates in Photocatalytic Degradation of Pentachlorophenol by Continuous Flow Chemiluminescence

Abstract: Photocatalytic degradation is a powerful technique for the decomposition of pollutants. However, toxic intermediates might be generated which have become a great concern recently. In the present work, a continuous flow chemiluminescence (CFCL) method was developed for dynamic monitoring of toxic intermediates generated in the photocatalytic degradation of pentachlorophenol (PCP). Among the main intermediates, tetrachloro-1,4-benzoquinone (TCBQ) and trichlorohydroxy-1,4-benzoquinone (OH-TrCBQ) showed higher or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 47 publications
(115 reference statements)
0
10
0
Order By: Relevance
“…The results were in good agreement with those obtained by the LC-MS method (Table S1). Moreover, the detection limits of earlier reported methods for the hydroxylated intermediates were between 0.5 and 0.05 μM. Therefore, it was concluded that the proposed method was a sensitive method.…”
Section: Resultsmentioning
confidence: 84%
“…The results were in good agreement with those obtained by the LC-MS method (Table S1). Moreover, the detection limits of earlier reported methods for the hydroxylated intermediates were between 0.5 and 0.05 μM. Therefore, it was concluded that the proposed method was a sensitive method.…”
Section: Resultsmentioning
confidence: 84%
“…Wastewater is mostly produced from the emissions of a wide range of organic contaminants, which are widespread in industrial, agricultural, and household applications 2,3 . The removal of organic pollutants from wastewater is currently a primary challenge to circumvent the world's water crisis, owing to their high resistance to biodegradation 4 . 2,4-Dinitrophenol (DNP) has been known as a priority pollutant because of its mutagenic and carcinogenic nature and bioaccumulation 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Current research on photocatalytic water remediation is focused on the development of sustainable materials and the improvement in the degradation efficiency towards targeted pollutants, but it does not include the elimination of possible risk of environmental assessment 37,38 . Even after the complete degradation of organic pollutants, acute toxicity has been observed owing to the generation of toxic byproducts 4 . Therefore, the determination of the concentration of DNP in treated water may not be sufficient, and an accurate environmental risk assessment is highly desirable to evaluate the overall efficiency of wastewater treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to photocatalysis, photoelectrocatalysis (PEC) has been used as an effective way to remove organic pollutants and produce H 2 because of the rapid separation of photoelectrons from holes under the bias voltage. The photogenerated electrons can be rapidly transferred to the cathode to form a photocurrent or drive reduction reactions such as H 2 generation and CO 2 reduction, and the holes left on the anode are used for oxidative degradation of POPs. Thus, a new photocatalytic fuel cell (PFC) based on the entire process can be constructed for simultaneous electricity generation and pollutant degradation. …”
Section: Introductionmentioning
confidence: 99%